2018
DOI: 10.4081/ejtm.2018.7278
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of combined endurance and resistance training in Amyotrophic Lateral Sclerosis: A pilot, randomized, controlled study

Abstract: Based on available evidence, muscle strengthening and cardiovascular exercises can help maintain function and not adversely affect the progression of disease in patients with ALS. However, this evidence is not sufficiently detailed to recommend a specific exercise prescription. The purpose of this project was to assess clinical outcomes of a combined exercise programme to increase knowledge of rehabilitation in ALS patients. 38 ALS patients were assigned randomly to two groups: one group underwent a specific e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 35 publications
0
49
0
1
Order By: Relevance
“…In another study, conducted in a few SLA patients with respiratory failure, exercise slowed the clinical deterioration of the disease [28]. Current studies support the effectiveness of exercise in patients with motoneuron disease: two recent clinical trials in ALS patients [9,29] demonstrated safety and tolerability of resistance and endurance training. Lunetta and collaborators [30] proved that monitored exercise programs reduce motor deterioration.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In another study, conducted in a few SLA patients with respiratory failure, exercise slowed the clinical deterioration of the disease [28]. Current studies support the effectiveness of exercise in patients with motoneuron disease: two recent clinical trials in ALS patients [9,29] demonstrated safety and tolerability of resistance and endurance training. Lunetta and collaborators [30] proved that monitored exercise programs reduce motor deterioration.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies suggest that skeletal muscle contributes to a retrograde signaling cascade that impairs motor neurons [6][7][8]. In a trial [9] we found that regular, rehabilitative exercise in ALS patients helps to reduce pain and fatigue of skeletal muscle origin. If a patient is inactive, the loss of training and disuse leads to muscular atrophy, which adds to the weakness and muscular atrophy caused by denervation and degeneration of motor neurons in ALS.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…A number of clinical trials showed the benefit of physical exercise in ALS patients. In a recent study, a significant increase of the score of the functional independence scale was observed in ALS patients after a specific program training in which improvement of oxygen consumption, muscle strength and fatigue was reported [125]. An ALS-like condition was observed in old people [126] where physical exercise determined re-innervation of muscle fibers at neuromuscular junctions normally reduced by aging [126].…”
Section: Sirtuins In Neurodegenerative Disorders Of Interest For Rehamentioning
confidence: 98%